PRELIMINARY SURVEY ON THE DEMAND FOR FACIAL REJUVENATION THREAD-EMBEDDING THERAPY IN TRADITIONAL MEDICINE (Vietnam Journal of Community Medicine, 2026)
Objective: To conduct a preliminary survey on the demand for the application of facial rejuvenation thread-embedding therapy in Traditional Medicine among patients and Traditional Medicine physicians at Can Tho Traditional Medicine Hospital.Methods: A cross-sectional descriptive study was performed on 385 patients and 30 Traditional Medicine physicians at Can Tho Traditional Medicine Hospital from November 2023 to May 2024. Data were collected using a structured questionnaire based on the Health Belief Model (HBM) and analyzed with SPSS version 20.0.Results: A total of 65.7% of patients and 86.7% of Traditional Medicine physicians expressed demand for facial rejuvenation thread-embedding therapy. Patients mainly valued the method's safety (54.5%) and rejuvenation effectiveness (73.8%), while the primary barrier was the high treatment cost (29.7%). For physicians, the primary barrier was the lack of specialized training (100%), although most were confident and willing to implement the method if provided with adequate professional support.Conclusion: Both patients and Traditional Medicine physicians perceive facial rejuvenation thread-embedding therapy as a feasible and valuable technique for health enhancement and aesthetic care in Traditional Medicine. Further efforts should focus on technical training, procedural standardization, and interventional clinical studies to promote broader community implementation.